PENENTUAN KONDISI OPTIMUM FERMENTASI MENGGUNAKAN LACTOBACILLUS BULGARICUS DALAM PEMBUATAN TEPUNG SUWEG (AMORPHOPHALLUS CAMPANULATUS) TERFERMENTASI - Prasetyawan, Sasangka; Sutrisno, Sutrisno; Suhaili, Ahmad (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
ABSTRACT This aims of this study is to determine the optimum conditions and characteristics of fermented suweg flour. The optimum conditions are determined based on the maximum levels of lactic acid produced in the fermentation process. Fermentation conditions are studied based on the variation of pH (3,4,5,6,7), temperatur (30oC, 35oC, 40oC, 45oC, 50oC) and incubation time (3,6,9,12,15 hours) The characteristic of fermented and non fermented suweg flour include starch, amylase, amylopectin and expands power. The optimum fermentation conditions achieved at pH 6, temperatur 45°C, and 12 hours of incubation time. The characteristics of fermented suweg flour at the optimum conditions reach higher starch, amylose, amylopectin and expands power, better than non fermented flour. The contents of starch, amylose, and amylopectin in the non fermented suweg flour are 83.7%, 11.72%, 71.98% respectively. The content of starch, amylose, and amylopectin in fermented suweg flour are 87.3%, 12.15%, 74.82% respectively. Expands power of non fermented suweg flour is 35.29%, while expands power in fermented suweg flour is 41.18%. Key words: Fermentation, Flour, Lactobacillus bulgaricus, Suweg